СПЕЦИФИКА ПЕРЕДАЧИ БЕЗ ЭКВИВАЛЕНТНОЙ ЛЕКСИКИ - Исаева, Ш.М. (SCIENCE and SOCIETY, 2020)
The work of Yusuf hos Khojib “Kutadgu Bilig” does not lose its relevance at the present time, arousing the interest of scientists of various fields, including linguists. This article discusses the translation of such equivalent lexemes as Kalyam, Vezir, Chigil, Chovgan, Tamga into Russian and English. For illustration, are provided in the article fragments of the Russian translation by S.N. Ivanov and the English translation of Robert Dankoff.
Keywords: lexeme; vocabulary; translation; non-equivalent vocabulary; transcription; transliteration